Cigarette Affordability in the Russian Federation 2002-2017 - Zheng, Rong (World Bank, Washington, DC, 2018)
The goal of this study is to examine cigarette affordability in Russia between 2002 and 2017 in order to provide an understanding of the country's current tobacco excise tax policy, and to identify opportunities and next steps.